ELTV Channel 6 News (African Knowledges and the History Publication since the 1970s)
News on material and food (production) scarcity in Liberia; the Red Cross Society in Liberia; and plastic recycling via the work of rubber-slipper artisans.
Keywords: News; Public Affairs